Fire Safety Analysis of Nanjing Yangtze River Tunnel Based on Fault Tree and Triangle Fuzzy Theory. (2018) - Zhang, Chun-yan; Tao, Gang; Zhang, Li-jing
Abstract: In order to realistic study of fire accidents in tunnel, according to the uncertainty and fuzziness of accident, the model of fault tree is established for Nanjing Yangtze River Tunnel after Nanjing Yangtze River Bridge closed, and with the triangular fuzzy theory, the estimate of base event is obtained by scoring of the relevant professional, and the probable range of top event is calculated. In addition, the fuzzy importance is obtained by the median method of triangular fuzzy theory, to find the fuzzy importance of basic event. Then the fire prevention measures are proposed for Nanjing Yangtze River Tunnel. The results show that the possibility of uncontrolled fire is small in Nanjing Yangtze River Tunnel. Among them, fire rescue no arriving in time, no knowledge of fire extinguishing, vehicle collision on fire and auto-alarm failure are main factors leading to catastrophic fire. Thus, it is of great significance to strengthen the fire-fighting knowledge of personnel and the capacity of automatic fire-fighting for the tunnel itself, to reduce the occurrence of fire in tunnel.